MK17, a specific marker closely linked to the gynoecium suppression region on the Y chromosome in Silene latifolia - Hobza, Roman; Hrusakova, Pavla; Safar, Jan; Bartos, Jan; Janousek, Bohuslav; Zluvova, Jitka; Michu, Elleni; Dolezel, Jaroslav; Vyskot, Boris (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2006)
The aim of this work was to isolate new DNA markers linked to the Silene latifolia Y chromosome. To do this we created a chromosome-specific plasmid library after DOP-PCR amplification of laser-microdissected Y-chromosomes. The library screening led to the isolation of several clones yielding mostly to exclusive male specific hybridization signals. Subsequent PCR confirmed the Y-unique linkage for one of the sequences. This DNA sequence called MK17 has no homology to any known DNA sequence and it is not expressed. Based on PCR and Southern analyses, MK17 is present only in dioecious species of the Elisanthe section of the genus Silene (S. latifolia, S. dioica, and S. diclinis) and it is absent in related gynodioecious and hermaphroditic species. The mapping analysis using a panel of deletion mutants showed that MK17 is closely linked to the region controlling suppression of gynoecium development. Hence MK17 represents a valuable marker to isolate genes controlling the gynoecium development suppression on the Y chromosome of S. latifolia.
Keywords: Sequence Deletion; Southernův blotting; Y Chromosome; DNA primery; sekvence nukleotidů; chromozom Y; sekvenční delece; polymerázová řetězová reakce; Base Sequence; Polymerase Chain Reaction; Blotting, Southern; DNA Primers; Silene